Behavioral Aspects of Communication in Organizations - Fortuna Casoria; Arno Riedl; Peter Werner (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper reviews experimental studies that investigate the effects of communication on be-havior in organizational settings. Two main classes of studies are identified: (a) studies on coordination and competition, which include experimental research that tests whether com-munication can help to overcome coordination failure within organizations, and (b) studies that analyze the role of communication in alleviating problems arising from information asym-metries at the workplace. The evidence from these studies indicates that communication is suited to improve efficient coordination within firms and to mitigate information problems in employer-employee relationships. In addition, studies are presented that focus on the interac- tion between communication and monetary incentive schemes in companies.
Keywords: C90; D82; D83; J53; 330; communication; organization; experiment; behavior